Why Women Living in an Obstetric Care Underserved Area Do Not Utilize Their Local Hospital Supported by Korean Government for Childbirth - Jung-Eun Kim, PhD; Baeg Ju Na, MD, PhD; Hyun Joo Kim, RN, PhD; Jin Yong Lee, MD, PhD, MHA (Elsevier, 2016)
Purpose: This study aimed to understand why mothers do not utilize the prenatal care and delivery services at their local hospital supported by the government program, the Supporting Program for Obstetric Care Underserved Area (SPOU). Methods: We conducted a focus group interview by recruiting four mothers who delivered in the hospital in their community (a rural underserved obstetric care area) and another four mothers who delivered in the hospital outside of the community. Results: From the finding, the mothers were not satisfied with the quality of services that the community hospital provided, in terms of professionalism of the obstetric care team, and the outdated medical device and facilities. Also, the mothers believed that the hospital in the metropolitan city is better for their health as well as that of their babies. The mothers who delivered in the outside community hospital considered geographical closeness less than they did the quality of obstetric care. The mothers who delivered in the community hospital gave the reason why they chose the hospital, which was convenience and emergency preparedness due to its geographical closeness. However, they were not satisfied with the quality of services provided by the community hospital like the other mothers who delivered in the hospital outside of the community. Conclusions: Therefore, in order to successfully deliver the SPOU program, the Korean government should make an effort in increasing the quality of maternity service provided in the community hospital and improving the physical factors of a community hospital such as outdated medical equipment and facilities.